Mitochondria‐targeted antioxidant mitoquinone deactivates human and rat hepatic stellate cells and reduces portal hypertension in cirrhotic rats. (27th April 2017) - Vilaseca, Marina; García‐Calderó, Héctor; Lafoz, Erica; Ruart, Maria; López‐Sanjurjo, Cristina Isabel; Murphy, Michael P.; Deulofeu, Ramon; Bosch, Jaume; Hernández‐Gea, Virginia; Gracia‐Sancho, Jordi; García‐Pagán, Juan Carlos
Abstract: Background & Aims: In cirrhosis, activated hepatic stellate cells (HSC) play a major role in increasing intrahepatic vascular resistance and developing portal hypertension. We have shown that cirrhotic livers have increased reactive oxygen species (ROS), and that antioxidant therapy decreases portal pressure. Considering that mitochondria produce many of these ROS, our aim was to assess the effects of the oral mitochondria‐targeted antioxidant mitoquinone on hepatic oxidative stress, HSC phenotype, liver fibrosis and portal hypertension. Methods: Ex vivo: Hepatic stellate cells phenotype was analysed in human precision‐cut liver slices in response to mitoquinone or vehicle. In vitro: Mitochondrial oxidative stress was analysed in different cell type of livers from control and cirrhotic rats. HSC phenotype, proliferation and viability were assessed in LX2, and in primary human and rat HSC treated with mitoquinone or vehicle. In vivo: CCl4 ‐ and thioacetamide‐cirrhotic rats were treated with mitoquinone (5 mg/kg/day) or the vehicle compound, DecylTPP, for 2 weeks, followed by measurement of oxidative stress, systemic and hepatic haemodynamic, liver fibrosis, HSC phenotype and liver inflammation. Results: Mitoquinone deactivated human and rat HSC, decreased their proliferation but with no effects on viability. In CCl4 ‐cirrhotic rats, mitoquinone decreased hepatic oxidative stress, improved HSC phenotype, reduced intrahepatic vascular resistance and diminished liver fibrosis. These effects were associated with a significant reduction in portal pressure without changes in arterial pressure. These results were further confirmed in the thioacetamide‐cirrhotic model. Conclusion: We propose mitochondria‐targeted antioxidants as a novel treatment approach against portal hypertension and cirrhosis. Abstract : See Editorial on Page963